Analysis of Synaptic Signal Transmission Based on a Kinetic Model - Vasyliev, O.M.; Zaitseva, O.V.; Chalyi, O.V. (Ukrainian Journal of Physics, 2024)
We will analyze the peculiarities of the nerve signal transmission through a synaptic cleft (a contact between two neurons). The corresponding analysis is performed using a kinetic model that is based on a system of nonlinear differential equations of the first order and makes it possible to calculate the number of activated receptors on the postsynaptic membrane and the amount of mediator in the synaptic cleft. The model combines simplicity and functionality, which allows obtaining the qualitative results comparable to available experimental data and the results of other theoretical studies. It has been shown that the model correctly describes the process of signal transmission through the synaptic cleft at a qualitative level. Exact (numerical) and approximate (analytic) solutions for the number of activated receptors on the postsynaptic membrane and the amount of a mediator in the synaptic cleft are obtained and analyzed. The stability of stationary states is considered and proved in the framework of the proposed model, which confirms the self-consistency of the model and the possibility of its use for simulating the signal transmission through the synapse.